L’impossible retour dans la Marâtre patrie de Michalis Ganas : lieux de précarité ; lieux d’altérité - Théodouli (Lily) Alexiadou (Cahiers Balkaniques)
This paper approaches the narrative work of the poet of the 1970s generation Michalis Ganas and focuses on the concepts of exile, expatriation and migration as biographical events as well as psychic and literary imprints. Ganas and his family belonged to the group of Epirotes who during the Civil War in 1948 were deported to socialist countries and ended up in the village of Bellogianni in Hungary, from where they returned to Greece in 1954. In his novel StepMotherland (1981) he narrates memories of his childhood years of exile and the difficult conditions of his return to a “motherland” marked by political persecution, economic poverty and emigration. The aim of our study is to explore the multiple aspects of foreignness and locality in the work of Michael Gunnas: expatriation, return, internal migration, existential exile. Situations both real and literary, which are linked to places, but, at the same time, imposed by the course of the poetic ego through time, its age and poetic maturity.